Anatomical liver resection of segment 4a en bloc with the caudate lobe. Issue 6 (18th February 2016) - Silvestrini, Nicola; Coppola, Alessandro; Ardito, Francesco; Nuzzo, Gennaro; Giuliante, Felice
Abstract : Anatomical segmentectomy is the complete resection of an area supplied by a segmental portal branch. Among segmentectomies, isolated segmentectomy 4 is a technically demanding procedure because there are two transection planes: on the left side along the umbilical fissure and, on the right side, along the middle hepatic vein. Although there are several reports on anatomic segmentectomies, only few regard the anatomic segmentectomy 4a. We report here the case of a 60‐year‐old man who underwent anatomical segmentectomy 4a en bloc with the caudate lobe to resect a colorectal liver metastasis located in segment 4a and involving the paracaval portion of the caudate lobe. This type of procedure was planned in order to maximize the postoperative functional hepatic reserve, thereby reducing the risk of postoperative liver failure and ultimately allowing the possibility for future repeat hepatectomy in case of recurrence. J. Surg. Oncol. 2016;113:665–667 . © 2016 Wiley Periodicals, Inc.